1998
DOI: 10.1074/jbc.273.48.31680
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Isoleucyl-tRNA Synthetase from Staphylococcus aureus

Abstract: The kinetic mechanism for the amino acid activation reaction of Staphylococcus aureus isoleucyl-tRNA synthetase (IleRS; E) has been determined from stoppedflow measurements of the tryptophan fluorescence associated with the formation of the enzyme-bound aminoacyl adenylate (E⅐Ile-AMP; Scheme 1). Isoleucine (Ile) binds to the E⅐ATP complex (K 4 ‫؍‬ 1.7 ؎ 0.9 M) ϳ35-fold more tightly than to E (K 1 ‫؍‬ 50 -100 M), primarily due to a reduction in the Ile dissociation rate constant (k -1 Ϸ 100 -150 s ؊1 , cf. k -4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Moreover, characterization of the IleRS reaction cycle (12) showed that binding of Ile and ATP is thermodynamically linked, making this factor more important. Rather than seeking an analytical solution to this problem, we approached it through numeric simulation techniques, using the reaction state model that we had developed for binding and activation of substrates by IleRS (12). Simulations of steadystate inhibition predicted that compounds which competed with both Ile and ATP would yield linear competitive inhibition kinetics (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, characterization of the IleRS reaction cycle (12) showed that binding of Ile and ATP is thermodynamically linked, making this factor more important. Rather than seeking an analytical solution to this problem, we approached it through numeric simulation techniques, using the reaction state model that we had developed for binding and activation of substrates by IleRS (12). Simulations of steadystate inhibition predicted that compounds which competed with both Ile and ATP would yield linear competitive inhibition kinetics (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore also characterized the kinetics of substrate binding and activation in some detail. This work is reported in an accompanying paper (12) and the results summarized in the scheme given in Table I. The purpose of this was 3-fold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Design-For simplicity, the following analysis is based on the TyrRS system; comparative analyses on the isoleucyl-and threonyl-tRNA synthetases have been reported [43,74]. Rate and dissociation constants refer to the reaction mechanism shown in Figure 8.…”
Section: Methodsmentioning
confidence: 99%
“…Most pre-steady-state kinetic studies of tRNA synthetases have addressed the adenylate synthesis step, which proceeds independently of tRNA for most of the enzymes (30)(31)(32)(33)(34). However, early studies of MetRS, PheRS, TyrRS, ArgRS, and TrpRS used chemical-quench flow to examine aminoacylation with 14 C-labeled amino acid (35)(36)(37)(38)(39).…”
Section: Assay For Steady-state and Single-turnover Aminoacylation Kimentioning
confidence: 99%